Impact of Temporal Diversity on Team Process and Team Effectiveness. - Kramer, Julia (My University, 2009)
Teams are increasingly important in today's business world. Our research heeds the call to go beyond "surface-level" demographics like age and gender to study one form of "deep-level diversity;" specifically, temporal diversity. Here, we examine how six individual temporal characteristics impact team process and effectiveness: polychronicity, time urgency, temporal depth and focus, punctuality, and scheduling/deadline preferences.
Color poster with text, chart, and graph describing research conducted by Julia Kramer, advised by Rhetta L. Standifer.
Keywords: Teams in the workplace; Diversity in the workplace; Time--Social aspects; Time perception; Posters